2023
DOI: 10.1111/ijcs.12893
|View full text |Cite
|
Sign up to set email alerts
|

Masstige marketing: Addressing short‐term and long‐term happiness

Abstract: Consumers must manage their experiences to achieve their goals. It is currently unclear how masstige products are involved in these experiences. This study experimentally examines the relationships between self‐control, self‐indulgence, intention to purchase a masstige product, and both short‐ and long‐term happiness. In total, 319 consumers participated in this experiment. This study compared four models addressing these relationships and concluded that a higher level of self‐control leads to a lower level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 119 publications
2
4
0
Order By: Relevance
“…In another study, it shows a significant relationship between masstige brands and brand happiness (Kumar et al, 2021). Supporting previous research found that the intention to buy masstige products affects short-term happiness (Burhanudin, 2023).…”
Section: Brand Happinesssupporting
confidence: 61%
See 1 more Smart Citation
“…In another study, it shows a significant relationship between masstige brands and brand happiness (Kumar et al, 2021). Supporting previous research found that the intention to buy masstige products affects short-term happiness (Burhanudin, 2023).…”
Section: Brand Happinesssupporting
confidence: 61%
“…This is based on previous study which found a significant influence between purchase intention and brand happiness (Hwang & Han, 2014). Purchase intention in the concept of masstige brands can foster attitudinal loyalty and further create brand happiness (Burhanudin, 2023). Referring to these arguments, this study formulates the Hypothesis 3.…”
Section: Willingness To Purchase a Masstige Brand And Brand Happinessmentioning
confidence: 82%
“…Studies have proven that masstige can enable not only the measurement of brand prestige but also brand equity (Alagarsamy et al, 2022; Paul, 2018, 2019). In addition, brand masstige has a role in explaining purchase intention (Burhanudin, 2023; Park et al, 2022). Based on the aforementioned articles, we can conclude that proper brand management can contribute to an increase in brand masstige and brand equity and thus higher brand sales.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…The existing studies on masstige noted that masstige is for the masses, affordable, not rare, and prestigious (Ishaq et al, 2023; Kumar et al, 2019). Kim et al (2019) presented a semiotic analysis of the advertisement for masstige brands, while Paul (2019) stated that masstige brands can be developed by adopting a masstige marketing strategy grounded on the four P s. Despite these studies, the theoretical foundation of masstige is noticeably weak; research is scarce regarding antecedents on masstige purchase intentions from a consumer perspective (Burhanudin, 2024; Ishaq et al, 2023; Kumar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%